Determinatıon of the MSTN/HaeIII gene polymorphism in indigenous Morkaraman sheep - Saygili, E; Ozdemir, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study was to examine the polymorphic structures of the Myostatin (MSTN) gene locus in the native Morkaraman sheep, and to determine the distribution of genotype and allele frequencies. MSTN/HaeIII gene polymorphisms were identified in DNA isolated from blood samples from 262 Morkaraman sheep used in the study, using the PCR-RFLP method. According to the Hardy-Weinberg genetic balance test, it was observed that the distribution of genotype frequencies was not in balance (P<0.01) in the population studied. The MM, Mm and mm genotype frequencies of the MSTN gene in the population were determined as 11.1%, 62.6% and 26.3%, respectively, the frequencies of the M and m allele was 0.42 and 0.58 respectively. Observed heterozygosity (Ho) calculated for MSTN in the whole population was significantly higher than expected heterozygosity (He) values. Observed heterozygosity (Ho) calculated for MSTN in the whole population was significantly higher than expected heterozygosity (He) values.While the FIS value was found as -0.312, the FIT value was determined as -0.303. The genotype and allele frequencies determined in terms of MSTN gene polymorphism were sufficient to reveal the genotype diversity of the breed.